2017
DOI: 10.1021/acs.orglett.7b02721
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Reversible Oxidation of N-Peralkyl-Substituted NHC–CAAC Derived Triazaalkenes: Isolation of Radical Cations and Dications

Abstract: Herein, the isolation and characterization of N-peralkyl-substituted NHC-CAAC derived triazaalkenes in three oxidation states, neutral, radical cation, and dication, are reported. Cyclic voltammetry has shown the reversible electronic coupling between the first and second oxidation to be ΔE = 0.50 V. As a proof-of-principle, to demonstrate the electron-rich nature of the triazaalkene, it was shown that it can be used as an electron donor in the reduction of an aryldiazonium salt to the corresponding arene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Organic cationic radicals [ Me2 cAAC-NHC]˙ + OTf – ( 34 , Fig. 7) were obtained from the one-electron oxidation of the NHC-cAAC heterodimers which were synthesized by the reaction of NHC with a cyclic iminium salt, followed by deprotonation 23. X-band EPR measurements of the radical cations ( 34 ) in THF at room temperature revealed that the unpaired electron couples with all the three nitrogen atoms as indicated by the presence of hyperfine coupling [ 34a : 16.8, 13.2, and 12.0 MHz; 34b : 19.8, 12.7, and 10.4 MHz].…”
Section: Group 14 Radicalsmentioning
confidence: 99%
“…Organic cationic radicals [ Me2 cAAC-NHC]˙ + OTf – ( 34 , Fig. 7) were obtained from the one-electron oxidation of the NHC-cAAC heterodimers which were synthesized by the reaction of NHC with a cyclic iminium salt, followed by deprotonation 23. X-band EPR measurements of the radical cations ( 34 ) in THF at room temperature revealed that the unpaired electron couples with all the three nitrogen atoms as indicated by the presence of hyperfine coupling [ 34a : 16.8, 13.2, and 12.0 MHz; 34b : 19.8, 12.7, and 10.4 MHz].…”
Section: Group 14 Radicalsmentioning
confidence: 99%
“…The calculations show that 3 H / 3 Me are slightly more stable than [ 8 H ]/[ 8 Me ] species, while 6 H / 6 Me are slightly more stable than [ 5 H ]/[ 5 Me ]. When 3 H / 3 Me and 6 H / 6 Me were mixed in a 1:1 ratio in THF no reaction took place, which is in contrast to NHC‐CAAC derived triazaalkenes, which undergo comproportionation reactions . Even though the interconversion between the reduced and oxidized species is reversible, the forward and the backward reaction pathways are completely distinct.…”
Section: Resultsmentioning
confidence: 94%
“…go comproportionation reactions. [24] Even though the interconversion between the reduced and oxidized species is reversible, the forward and the backward reaction pathways are completely distinct. Still, the interconversion of 3 H /3 Me and 6 H / 6 Me can be considered globally reversible even though the second redox events in each direction are individually electrochemically irreversible.…”
Section: Resultsmentioning
confidence: 99%
“…To rule out the possibility of formation of compound 7 by nucleophilic amination, we reacted compound 2 with an excess of i PrNH 2 , which resulted in no reaction. It may be mentioned that when we reacted sterically less hindered N‐alkyl substituted NHCs, 1,3,4,5‐Me 4 ‐imidazole‐2‐ylidene and 1,3‐ i Pr 2 ‐4,5‐Me 2 ‐imidazole‐2‐ylidene, with compound 2 , normal addition occurred …”
Section: Resultsmentioning
confidence: 99%
“…It may be mentioned that when we reacteds terically less hindered Nalkyl substituted NHCs, 1,3,4,5-Me 4 -imidazole-2-ylidenea nd 1,3-iPr 2 -4,5-Me 2 -imidazole-2-ylidene, withc ompound 2,n ormala ddition occurred. [14] The calculated free energy at the B3LYP/TZVP level of theory [15] for the formation of compounds 4 and 5 from sub-Scheme1.Synthesis and possible mechanism for the formationo fc ompound 3. strates 1 and 2 was marginally endothermic by DG 298 = 6.2 kcal mol À1 ,w hich is in line with the estimated pK a values of the C2ÀHm oiety of compounds 2 (pK a = 27.9) and 4 (pK a = 23.3); however, this is much lower than the energy involved in the isomerization of compound 1 into 6 (DG 298 = 14.1 kcal mol À1 ). [13] On the other hand, the formation of compound 3 from species 4 and 5 is at hermoneutral reaction( DG 298 = 0.6 kcal mol À1 ).…”
Section: Introductionmentioning
confidence: 99%